Skills and knowledge for improved livelihoods and living standards (New Delhi, 2007)
This collaboration between UNDP and DST has been articulated through two programmes: the earlier VOTEG or Vocational Training for Employment Generation and now SKILLS, or Skills and Knowledge for Improved Livelihoods and Living Standards. Apart from demonstrating that PPPs can be effective vehicles for delivering quality training at the lower end of the skill spectrum, SKILLS has shown that despite being market-oriented, such programmes can be designed to meet larger social objectives like empowering women. SKILLS has also shown that Information Technology can be an invaluable tool for a mass outreach programme for imparting training. SKILLS will play an important role in ensuring that the nation fulfils its commitment of empowering the youth with skills and making them employable.
Keywords: Economic development